Application of genetically encoded indicators to mammalian central nervous system - Yoshiyuki Yamada (Frontiers Research Topics, 2016)
Genetically encoded indicators emerged as promising tools for cell type-specific and chronic recording of neuronal population activity. Since publication of the first prototypical genetically encoded Ca2+ indicators (Cameleons) in 1997, we have witnessed remarkable evolution of the field, with rapid improvement of indicator performance as well as expanded application to many model organisms in the neuroscience community. Challenges still remain, however, concerning the mammalian central nervous system: limited sensitivity of indicators to subtle changes in activity, slow signal kinetics, cytotoxicity after a long-term and high-level expression of indicators, and variable performance across cell types. In addition to improvement of the indicators per se, development of strategies that allow combined use of the indicators and optogenetic tools is also desired. In this Research Topic, we recruited top researchers in the field and their young colleagues to present their cutting-edge research as well as insightful opinions on the following subtopics: 1) Latest breakthroughs on development of genetically encoded indicators 2) Novel scientific findings obtained with genetically encoded indicators 3) Wishlist for the next-generation genetically encoded indicators 4) Guideline for selecting an appropriate indicator 5) Optimal methodology for indicator delivery to mammalian CNS